Making sense of the message: An analysis of the editor’s letter in three archetypal South African women’s magazines at the start of the 21st century - Rossouw, Elna (Stellenbosch : Stellenbosch University, 2021)
Thesis (DPhil)--Stellenbosch University, 2021.